Modelling the Great Australian Bight Ecosystem. (November 2018) - Fulton, E.A.; Bulman, C.M.; Pethybridge, H.; Goldsworthy, S.D.
Abstract: The Great Australian Bight Research Program has generated extensive new knowledge about the Great Australian Bight (GAB) system. Integrating disparate datasets (including old and new knowledge) is a challenge for any location, but is increasingly important given the expansion of the marine industries constituting the blue economy. This is particularly so when industries operate in frontier, or remote regions with high conservation significance. Ecosystem models are an integration tool that can give insight into the structure and function of marine systems and act as a testbed for exploring scenarios of development for the region. Two of the most widely used ecosystem models (Atlantis and Ecopath with Ecosim) were implemented for the GAB, to allow an exploration of development scenarios and to provide tools in support of future management of the GAB's socio-ecological systems. The models were used to evaluate the vulnerability of key species, food webs, habitats and animal groupings to ecosystem stressors such as climate change, fisheries, disease, changing spatial management, aquaculture and oil spills. The models' responses to cessation of fishing indicate that the anthropogenic signature is not 'untouched', but is not yet substantially degraded. The complexity and confined area of much of the natural and anthropogenic activity in the region, which is highly concentrated in the gulfs and along the shoreline, means the system is sufficiently interlinked for cumulative nonlinear outcomes to occur if the system is sufficiently stressed. Scenarios of increased fishing pressure had the greatest impacts on individual functional groups, while scenarios of ocean warming had the greatest influence on ecosystem structure and integrity. Oil spill scenarios (e.g. caused by potential off-shore shipping accidents) had potential impacts on seabirds, pelagic fishes and marine mammals, with flow-on effects to the whole ecosystem, but only in a confined area immediately around the incident's footprint. These results give scientists and managers insights into how expanding the blue economy could impact ecosystem services and the societies currently dependent on them. This work also provides a set of tools for the GAB that can act as a launch point for systems analysis and can facilitate future assessments or planning for the region.